An alien in the country of my birth: Xenophobia reinforcing otherness and promoting exclusion. Issue 2 (2nd April 2016) - Chandia, Margaret; Hart, Tim G. B.
Abstract: In South Africa xenophobia conjures up gruesome images of the 2008 and 2015 attacks. Physically violent attacks appear to make local and international headline news. But xenophobia is not simply about nationals and non-nationals, nor does it only occur as irregular violent outbreaks. Such portrayals obscure other far more widely lived experiences of xenophobia, which largely appear as a means of reinforcing otherness with the purpose of excluding such others from the benefits of citizenship or residence in South Africa. To understand this it is necessary to explore South Africa's xenophobic past, which has to do with continual struggles for limited resources. These struggles have not been effectively overturned by the removal of discriminatory apartheid legislation and the introduction of South Africa's Constitution. Our argument is based on author Margaret's experiences as a South African child born of middle-class immigrant parents, which are anchored in the broader political and social context of South Africa. These experiences produce the very real fear of being denied the Constitutional rights of a South African citizen or resident. Such fears are also experienced by South African citizens 'proper', and we include some evidence of this when it comes to interaction with naturalisation and police authorities, as well as what it means with regard to employment. While we have achieved a democracy, the next step is to move out of single-minded racial and ethnic silos to achieve a cosmopolitan democracy as envisaged in the Constitution.